10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: The effectiveness of routine health information systems (RHIS) depends significantly on the self-efficacy and actual competence of healthcare professionals in managing health information. Despite investments in health information infrastructure, gaps between perceived abilities and actual skills continue to undermine system performance. OBJECTIVE: This study assessed self-efficacy levels and competence gaps among healthcare professionals in RHIS tasks within Cape Coast Metropolis, Ghana. METHOD: A mixed-methods cross-sectional study was conducted among 265 healthcare professionals across 13 health facilities in the Metropolis. Self-efficacy was measured using a validated 7-item scale with responses ranging from 0 to 100. Actual competence was assessed through standardised paper-and-pencil tests across five RHIS task domains: data quality checking (verifying accuracy, completeness, and timeliness), statistical calculations (computing rates and percentages), data plotting and visualisation, interpretation of findings, and information utilisation for decision-making. Knowledge of RHIS rationale and problem-solving skills were also evaluated. Descriptive statistics, correlation analysis, and gap analysis were performed on the data. RESULTS: The mean self-efficacy score was 36.8% (95% confidence interval (CI) ± 2.22), with perceived confidence in calculating RHIS tasks showing the highest level (39.8%) and using data to make decisions showing the lowest (33.8%). Actual competence averaged 19.9% (95% CI ± 10.6), with calculation skills achieving the highest performance (28.1%) and plotting skills the lowest (11.9%). Significant gaps existed between self-efficacy and actual competence across all domains, with the largest gap in plotting (26%) and smallest in calculations (11.7%). Only 25% demonstrated adequate knowledge of data collection rationale, and fewer than 4% demonstrated adequate problem-solving skills. CONCLUSION: Substantial gaps exist between healthcare professionals' perceived self-efficacy and actual competence in health information management tasks in Cape Coast Metropolis. Persistent overconfidence, weak problem-solving skills, and limited understanding of data collection rationale collectively undermine RHIS performance.Implications for health information management practice:Targeted, practical capacity-building programmes addressing both technical skills and self-assessment accuracy are urgently needed in Cape Coast Metropolis and comparable low- and middle-income countries settings.